Are the effects of informational interventions driven by salience? - Eric Bettinger; Nina Menezes Cunha; Guilherme Lichand; Ricardo Madeira (University of Zurich, Department of Economics, 2021)
Informational interventions have been shown to significantly change behavior across a variety of settings. Is that because they lead subjects to merely update beliefs in the right direction? Or, alternatively, is it to a large extent because they increase the salience of the decision they target, affecting behavior even in the absence of inputs for belief updating? We study this question in the context of an informational intervention with school parents in Brazil. We randomly assign parents to either an information group, who receives text messages with weekly data on their child's attendance and school effort, or a salience group, who receives messages that try to redirect their attention without child-specific information. We find that information makes parents more accurate about students' absences, and has large impacts on their attendance, test scores and grade promotion relative to the control group. Even though salience messages, in contrast, do not make parents morea ccurate about their children's absences, learning outcomes in the salience group improve by at least as much. We document that both interventions increase the extent to which parents participate in their children's school life, and lead them to independently acquire additional information about student performance. Our results have implications for the design of informational interventions across a range of domains.
Keywords: C93; D83; D91; I25; I31; 330; Information; salience; inattention